Relevance of Environmental, Institutional and Economic Developments for ASEAN-6 - Ikhlaq, Muhammad Waleed (2016)
Economic Growth is influenced by large number of factors and there is an ongoing debate on the extent to which some of these strong and more quantifiable variables are effective. In order to comprehensively discuss the mainstream determinants of Economic Growth explored through past literature, the study chose to focus on ASEAN-6 countries encompassing Singapore, Malaysia, Indonesia, Thailand, Philippines and Vietnam. By considering three decades from 1985 to 2014 period and dividing it into multiple time span, intention was to evaluate the performance of ASEAN region before and after Asian Financial Crisis, Dot-Com bubble and Global Economic Crisis to reveal the most important drivers of economic performance. Our empirical results suggest that ASEAN-6 region performed better after Post-Global Economic Crisis period due to its better economic integration both intra-regionally and with other economies like China, EU. We find that Through Pooled OLS method along with Random Effect and Fixed Effect as robustness techniques to judge the effectiveness of trade liberalization, financial deepening, environment quality, foreign direct investment and 5 components of institutional quality (IQ), empirical findings have reported both trade openness and C02 emissions to have the most profound and consistent role in fostering the productivity of the region studied throughout. However, financial deepening in the region failed to significantly impact the economic growth except for 2002-2006 period when it negatively affected the growth. Net FDI inflows proved to be insignificant throughout except for pre-Asian financial crisis period. While IQ index played unimportant role for ASEAN-6 region during last 3 decades, IQ indicators like better voice and accountability enhanced growth throughout, regulatory quality during post Asian and Global Economic periods considered, good government effectiveness and control of corruption damaged the economic activity during period 1997-2001. ASEAN-6 region is hence recommended to continue with free trade notion, promote environment friendly technology, look and improve key institutional indicators for the region, and strengthen financial systems, as means to enhance its role as contributor to the global economy.